2007
DOI: 10.2165/00003088-200746070-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluvoxamine on the Pharmacokinetics of Roflumilast and??Roflumilast??N-Oxide

Abstract: Co-administration of roflumilast and fluvoxamine affects the disposition of roflumilast and its active metabolite roflumilast N-oxide most likely via a potent dual pathway inhibition of CYP1A2 and CYP2C19 by fluvoxamine. The exposure increases observed for roflumilast N-oxide are suggested to be attributable to CYP2C19 co-inhibition by fluvoxamine and thus, are not to be expected to occur when roflumilast is co-administered with more selective CYP1A2 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 20 publications
3
44
0
2
Order By: Relevance
“…A previous population pharmacokinetic study has indicated that clearance of roflumilast was 19 % greater in male than in female, and the small differences in roflumilast clearance are related to body weight and sex-differential effects on CYP1A2 [15]. The results in the present study were in accordance with the published literature, and the differences between genders Table 3 Main pharmacokinetic parameters (mean ± SD) of roflumilast and roflumilast N-oxide following single (fasting and fed state) and multiple (fasting state) oral doses of 0.375 mg roflumilast (n = 12) The mean pharmacokinetic parameters (C max and AUC) for roflumilast and roflumilast N-oxide in Chinese, Caucasians [8] and Blacks [16] healthy subjects are summarized in Table 4. The values of C max and AUC in Chinese are similar to those in Blacks, but higher than those in Caucasians.…”
Section: Discussionsupporting
confidence: 90%
“…A previous population pharmacokinetic study has indicated that clearance of roflumilast was 19 % greater in male than in female, and the small differences in roflumilast clearance are related to body weight and sex-differential effects on CYP1A2 [15]. The results in the present study were in accordance with the published literature, and the differences between genders Table 3 Main pharmacokinetic parameters (mean ± SD) of roflumilast and roflumilast N-oxide following single (fasting and fed state) and multiple (fasting state) oral doses of 0.375 mg roflumilast (n = 12) The mean pharmacokinetic parameters (C max and AUC) for roflumilast and roflumilast N-oxide in Chinese, Caucasians [8] and Blacks [16] healthy subjects are summarized in Table 4. The values of C max and AUC in Chinese are similar to those in Blacks, but higher than those in Caucasians.…”
Section: Discussionsupporting
confidence: 90%
“…Neither roflumilast nor roflumilast N-oxide by themselves inhibit CYP3A4 or CYP1A2 (40). Other data suggest a low potential for roflumilast to interact adversely with other drugs including montelukast, erythromycin, ketoconazole, budesonide, albuterol, midazolam (40), and antacids containing magnesium hydroxide or aluminium hydroxide (59)(60)(61)(63)(64)(65)(66)(67). This is important to determine because inducers of CYP3A4 and CYP1A2 have the potential to increase the CL of roflumilast thereby lowering its efficacy.…”
Section: Contraindications Effect Of Food and Drug-drug Interactionsmentioning
confidence: 99%
“…Correspondingly, agents that are metabolized by the same system could compete with roflumilast and delay its inactivation, in effect raising its level. A number of studies have been performed to evaluate such drug-drug interactions and their potential for adverse reactions (59)(60)(61)(62)(63)(64)(65)(66)(67). The results published so far indicate that there is not a substantial effect of a range of potential agents and conditions on roflumilast levels.…”
Section: Safety Outcomesmentioning
confidence: 99%
“…• рифампицин (мощный индуктор CYP3A4) при одновременном назначении с рофлумиластом снижает активность рофлумиласта на 58 % [19]; • антидепрессант флувоксамин (Феварин), блоки руя одновременно несколько изоферментов CYP, увеличивает активность рофлумиласта на 69 % [20]. В отличие от рофлумиласта, теофиллин облада ет узким терапевтическим индексом (от 10 до 15 (20) мкг / мл) и не имеет активных метаболитов.…”
Section: рофлумиласт в сравнении с теофиллиномunclassified
“…В отличие от рофлумиласта, теофиллин облада ет узким терапевтическим индексом (от 10 до 15 (20) мкг / мл) и не имеет активных метаболитов. Поэтому некоторые факторы (возраст, сердечная не достаточность, прием ингибиторов микросомаль ных ферментов печени) способны повышать кон центрацию теофиллина в крови до токсического уровня (табл.…”
Section: рофлумиласт в сравнении с теофиллиномunclassified